Analysis of Lead Levels (Pb) Level of Knowledge and Attitude of Teachers Educational Toys in Kindagarten at Medan Labuhan District in 2023 - Nababan, Julita Margareta; Chahaya, Indra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Toy products are still consumer goods that are in great demand by the public. When toy paint peels off the particles into dust and will stick to the mouth, food and drink. The study was descriptive of the research sample population of 15 teachers with total sampling techniques. Samples of educational toys as many as 7 toys were tested in the laboratory. The results obtained by teachers in kindergarten are generally aged â‰¤ 40 is 8 teachers (53.3%), the last education of teachers is D3 / S1 is 14 teachers (93.3%), all teachers who teach in kindergarten are women (100%), the old teaching experience is around 1-10 years is 6 teachers (40.0%). The variable teacher knowledge is classified as medium is 7 teachers (46.7%), good is 4 teachers (26.7%) and bad is 4 teachers (26.7%). The variable of teacher attitude is classified good is 14 teachers (93.3%) and medium is 1 teacher (6.7%). Educational toys tested in the laboratory using AAS (atomic absorption spectrophotometry) tools showed that 100% of toys contained lead (Pb) with a range of 0.22-107.4 ppm. Advice to teachers not to buy toys of too flashy colors and parents can also supervise the way children play.